Contribution to the knowledge of some rare plant communities from the southwestern Iberian System - Rodríguez-Rojo, M. Pilar; Crespo, Guillermo; Madrigal, Jaime; Fernández-González, Federico (Lazaroa, 2012)
Several herbaceous communities from the southwestern Iberian System poorly known from the phytosociological perspective are documented and framed into their correspondent syntaxa, including calcareous (Epipactido palustris-Primuletum farinosae) and siliceous sedge fens (Caricetum echinato-nigrae), Nardus swards (Genisto anglicae-Nardetum strictae), and rush meadows (Deschampsio hispanicae-Juncetum effusi and Hyperico undulati-Juncetum acutiflori). We also validate an unpublished association for thyme scrub communities of the endemic Thymus leptophyllus subsp. izcoi, proper from siliceous substrates in the north and southwestern Iberian System.